TYPES OF BASALT FIBERS USED FOR DISPERSING REINFORCEMENT (Web of Discoveries: Journal of Analysis and Inventions, 2024)
With the production of fiber reinforced fiber concrete and fibrotemirbeton structures based on fiber, there are many R & D works aimed at ensuring the strength and reliability of buildings and structures. Compressible reinforced concrete made of dispersed reinforced fibrobeton based on Basalt fibers is one of the important tasks to carry out research in areas of increasing the deformability, tightness and strength of the elements.